Rapid Detection of Rare Deleterious Variants by Next Generation Sequencing with Optional Microarray SNP Genotype Data. Issue 9 (22nd July 2015) - Watson, Christopher M.; Crinnion, Laura A.; Gurgel‐Gianetti, Juliana; Harrison, Sally M.; Daly, Catherine; Antanavicuite, Agne; Lascelles, Carolina; Markham, Alexander F.; Pena, Sergio D. J.; Bonthron, David T.; Carr, Ian M.
<x xml:space="preserve">Abstract</x> AgileVCFMapper is able to identify autozygous regions in the exome data of consanguineous individuals. This allows disease genes present in their families to be rapidly mapped, with or without microarray SNP genotype data. Since exome data from the affected individuals may contain the deleterious variant, it is also possible to screen the exome data for possible pathogenic mutations.